1981
DOI: 10.1002/1097-0142(19810215)47:4<806::aid-cncr2820470429>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Supratentorial recurrences in medulloblastoma

Abstract: Four children with medulloblastoma had massive supratentorial recurrences in the region of the cribriform plate after adequate craniospinal irradiation. The pathogenesis of these recurrences is probably related to underdosage to this region by shielding of the eyes. This hypothesis was corroborated by autopsy findings in two other patients in whom subfrontal implants were histologically different from recurrences elsewhere. Two possible solutions to avoid this problem in the future are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…It is reasonable to assume that the olfactory nerve will be contained within a CTV that includes the cribiform plate, and this has already been discussed. 4,[19][20][21] We know that the optic nerves are surrounded by CSF to the back of the globe and that some RT planning techniques (tomotherapy) underdose this area unless it is specifically contoured as part of the CTV. 51 Neither our work nor the literature investigates whether there are meningeal reflections and CSF through the middle cranial fossa foramen, superior orbital fissure, ovale, rotundum and spinosum and this would be an interesting topic for further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reasonable to assume that the olfactory nerve will be contained within a CTV that includes the cribiform plate, and this has already been discussed. 4,[19][20][21] We know that the optic nerves are surrounded by CSF to the back of the globe and that some RT planning techniques (tomotherapy) underdose this area unless it is specifically contoured as part of the CTV. 51 Neither our work nor the literature investigates whether there are meningeal reflections and CSF through the middle cranial fossa foramen, superior orbital fissure, ovale, rotundum and spinosum and this would be an interesting topic for further research.…”
Section: Discussionmentioning
confidence: 99%
“…Studies report the risk of cribiform plate recurrence in patients undergoing CSI in the era before this was considered to be part of the target volume, or when it was underdosed owing to either inadequate technique or deliberate shielding of the eyes. 4,[19][20][21] The same technical errors also resulted in recurrences inferiorly in the frontal and temporal lobes, 21 and there is now a general consensus that these structures should be included in the target volume however RT is planned and delivered.…”
Section: Clinical Settingmentioning
confidence: 99%
“…Supratentorial lesions accounted for only 6% of recurrences. Recent reports, however, have indicated that supratentorial recurrences may be more common than previously assumed [21]. Two common patterns of treatment failure are illustrated in the cases reported in this study.…”
Section: Discussionmentioning
confidence: 42%
“…One patient had local recurrence in the posterior fossa, while the other patient had recurrence in the frontal lobe adjacent to the cribriform plate. Frontal lobe recurrence has also been reported in previous studies [21] and the importance of employing radiation fields which include the cribriform plate with generous margin has been stressed [21].…”
Section: Discussionmentioning
confidence: 71%
“…Isolated sub-frontal relapse may occasionally be seen following CS-RT, and this may be attributed to an inadequate radiation dose in the cribriform plate region [7]. Certainly when lateral shaped fields are used, the eye block component may shield this region.…”
Section: The Cribriform Platementioning
confidence: 99%